Age-related changes and sex differences in ankle plantarflexion velocity - Atsuki Kanayama; Saki Yamamoto; Ryoga Ueba; Mio Kobayashi; Toshimitsu Ohmine; Akira Iwata (Scientific Reports, 2023)
Abstract Ankle plantar flexors play a vital role in the mobility of older adults. The strength and velocity of plantarflexion are critical factors in determining walking speed. Despite reports on how age and sex affect plantarflexion strength, basic information regarding plantarflexion velocity is still lacking. This cross-sectional observational study investigated age-related changes and sex differences in plantarflexion velocity by comparing them with plantarflexion strength. A total of 550 healthy adults were classified into four age groups for each sex: Young (< 40 years old), Middle-aged (40–64 years old), Young-old (65–74 years old), and Older-old (≧ 75 years old). We measured plantarflexion velocity and strength in the long-sitting position using a gyroscope and a hand-held dynamometer, respectively. Two-way analysis of variance revealed no interaction between age and sex for either plantarflexion velocity or strength. Plantarflexion velocity exhibited a significant decline with aging, as did the plantarflexion strength. We found no significant sex differences in plantarflexion velocity in contrast to plantarflexion strength. The results indicated a significant decrease with age and no difference in plantarflexion velocity between males and females characteristic plantarflexion velocity. Understanding the characteristics of plantarflexion velocity could contribute to preventing a decline in mobility in older adults.